2017
DOI: 10.1177/1468798417745118
|View full text |Cite
|
Sign up to set email alerts
|

Changing the home literacy environment through participation in family literacy programmes

Abstract: This paper presents findings from a study of family literacy provision in England and focuses on the effects of family literacy programmes on the home literacy environment. The fieldwork took place between September 2013 and December 2014 and involved 27 school-based programmes for pupils aged between 5 and 7, and their parents. The study used mixed methods, which involved observations of family literary sessions, a quantitative pre- and post-survey of 118 parents, and pre- and post-telephone qualitative inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 51 publications
1
24
0
2
Order By: Relevance
“…Both variables constitute indicators commonly used to characterise the home limiting environment, along with the resources available at home. In relation to the latter, previous work has emphasised the association between the number of books available at home and reading comprehension (Harvey, ; Swain & Cara, ). Consistent with these results, the current research has identified the number of books at home as a particularly relevant variable for the explanation of reading comprehension, whether they are books in general or children's books.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both variables constitute indicators commonly used to characterise the home limiting environment, along with the resources available at home. In relation to the latter, previous work has emphasised the association between the number of books available at home and reading comprehension (Harvey, ; Swain & Cara, ). Consistent with these results, the current research has identified the number of books at home as a particularly relevant variable for the explanation of reading comprehension, whether they are books in general or children's books.…”
Section: Discussionmentioning
confidence: 99%
“…The parents' educational level is also a determining factor for the literacy development of children (Baker, 2013;Hofslundsengen et al, 2018;Yeo et al, 2014), being a predictor of linguistic skills and the development of children's emergent literacy (Bracken & Fischel, 2008). The number of books at home is another indicator of the reading performance of children (Griffin & Morrison, 1997;Harvey, 2016;Puglisi, Hulme, Hamilton, & Snowling, 2017), either the total amount of books (Mascarenhas et al, 2017;Sénéchal, 2012) or the number of children's books (Sénéchal, 2006;Swain & Cara, 2017). The amount of reading books depends in most of cases on the family's socioeconomic status (Merlo, Bowman, & Barnett, 2007).…”
Section: Reading Comprehension and Limiting Environmentmentioning
confidence: 99%
“…Parents' academic socialization includes parents' attitudes, values, goals, expectations, and beliefs about education as well as the opportunities and activities they make available to their children (Puccioni, 2015;Taylor et al, 2004). For example, Swain and Cara (2019) discussed the role that family resources, parental literacy beliefs and activities and attitudes, parental beliefs and understanding, and family literacy activities and practices play as part of the home literacy environment or parents' academic socialization. Hoover Dempsey et al (2005) discussed that parents must believe they have the relevant skills with which to assist their children, and the time to do so, to be involved in their children's education.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Since these reviews, the loss of federal funding to literacy agencies and organizations has been substantial, resulting in the closure or reduction some of these agencies and impacting how family programing is supported, in Canada (Shohet, 2012). While international research on family literacy program models and programmatic issues continues to evolve (Ihmeideh & Al-Maadadi, 2020; Rabkin et al, 2018; Swain & Cara, 2019), there is little current research addressing these topics in the Canadian context. Our study aimed to gauge the nature and availability of family-focused early learning opportunities for a diverse range of families within one Canadian context, and identify issues experienced by the community-based organizations offering these programs.…”
Section: Introduction and Purpose Of The Studymentioning
confidence: 99%